2020
DOI: 10.1007/s11858-020-01191-5
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom as a reform-oriented approach to teaching mathematics

Abstract: Innovative methods can change the paradigm of teaching mathematics and inspire teachers to espouse new ideas and gain new experiences. The flipped classroom (FC) is currently an innovative pedagogical approach that has high potential to transform the teaching of mathematics. In the case study described in this paper, we investigated one mathematics teacher’s transformation of teaching in two mathematics classrooms through implementing interventions based on FC methods; furthermore, we identified several key po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 33 publications
4
77
0
10
Order By: Relevance
“…In this issue Cevikbas and Kaiser ( 2020 ) describe how the implementation of a flipped classroom pedagogical approach enabled an experienced Turkish secondary school teacher to develop practices that aligned to a more socio-contructivist paradigm. This in-depth case study sheds light on how shifts in the quantity and quality of the teacher’s scaffolding and questioning techniques provided evidence of this evolution, whilst also highlighting the important affective component for the teacher involved.…”
Section: Concerning Classroom Practice—the Different and Emerging Plamentioning
confidence: 99%
“…In this issue Cevikbas and Kaiser ( 2020 ) describe how the implementation of a flipped classroom pedagogical approach enabled an experienced Turkish secondary school teacher to develop practices that aligned to a more socio-contructivist paradigm. This in-depth case study sheds light on how shifts in the quantity and quality of the teacher’s scaffolding and questioning techniques provided evidence of this evolution, whilst also highlighting the important affective component for the teacher involved.…”
Section: Concerning Classroom Practice—the Different and Emerging Plamentioning
confidence: 99%
“…In this regard, ElSaheli-Elhage (2021) noted that some educators admitted that they are not digitally literate enough to cope with regular online teaching activities during the pandemic. In this respect, Cevikbas and Kaiser (2020) pointed out another drawback related to digital teaching, which is closely linked to the subject-specific content needed for effective flipped teaching. They highlighted the problems for teachers in identifying adapted learning materials that successfully meet the specific needs of their students or in creating their own lecture videos, slides, infographics, and other learning resources via online platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already shown that flipped classroom approaches can improve student performance in science education (Sezer, 2017) as well as in mathematics education (Charles-Ogan & Williams, 2015;Wei et al, 2020). A recent study (Cevikbas & Kaiser, 2020) regarding flipping mathematics classes concludes that well-designed flipped classroom scenarios can support students' mathematical thinking and understanding by applying differentiated teaching strategies. In this paper, we are investigating the design of inquiry-based flipped classroom scenarios and present the development of a design heuristic supporting teachers' lesson planning practice.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For setting up an inquiry-based flipped classroom scenario, teachers need to plan on how to arrange in-class and out-of-class phases carefully. Recent research (Weinhandl, Lavicza & Houghton, 2020) indicates essential aspects for introducing STEM teachers and especially mathematics teachers (Cevikbas & Kaiser, 2020;Weinhandl & Lavicza, 2019) to flipped classroom approaches. However, there is still a lack of research investigating how to support STEM teachers' lesson planning practice for inquiry-based flipped classroom scenarios.…”
Section: Introductionmentioning
confidence: 99%